Risk analysis and assessment of efficiency of investment projects (Journal of Economic Research & Business Administration, 2015)
Risk analysis of investment projects is carried out for identification of the factors defining risk, and forecasting of their manifestation. Need of the analysis of design risks for modern conditions is caused, first of all, that the cash flows constructed on any innovative project belong to future periods and have expected character. Therefore the probability of unauthenticity of numerical data used for calculations, so, and results increases. Therefore, the account and an assessment of possible negative consequences of such mistakes becomes the most important part of examination. As the main instrument of similar researches the risk analysis of the project being the major component of examination of the innovative project and playing a significant role in decision-making on investment serves.
Keywords: risk; investment; innovation; efficiency; assessment; uncertainty